2005
DOI: 10.1111/j.1471-4159.2005.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β peptide enhances tumor necrosis factor‐α‐induced iNOS through neutral sphingomyelinase/ceramide pathway in oligodendrocytes

Abstract: Although accumulating evidence demonstrates that white matter degeneration contributes to pathology in Alzheimer's disease (AD), the underlying mechanisms are unknown. In order to study the roles of the amyloid-b peptide in inducing oxidative stress damage in white matter of AD, we investigated the effects of amyloid-b peptide 25-35 (Ab) on proinflammatory cytokine tumor necrosis factor-a (TNF-a)-induced inducible nitric oxide synthase (iNOS) in cultured oligodendrocytes (OLGs). Although Ab 25-35 by itself had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 53 publications
3
49
1
3
Order By: Relevance
“…Two forms of Aβ are generally used for in vitro studies, fibrillar and oligomer. Several studies suggest that fibrillar Aβ induces primary neuron apoptosis via the activation of NSM (Ayasolla et al, 2004;Chen et al, 2006;Jana and Pahan, 2004;Lee et al, 2004;Satoi et al, 2005;Zeng et al, 2005). However, our data using postmortem AD brain revealed that ASM, not NSM, activity was elevated.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Two forms of Aβ are generally used for in vitro studies, fibrillar and oligomer. Several studies suggest that fibrillar Aβ induces primary neuron apoptosis via the activation of NSM (Ayasolla et al, 2004;Chen et al, 2006;Jana and Pahan, 2004;Lee et al, 2004;Satoi et al, 2005;Zeng et al, 2005). However, our data using postmortem AD brain revealed that ASM, not NSM, activity was elevated.…”
Section: Discussioncontrasting
confidence: 80%
“…In vitro, Aβ has been shown to induce apoptosis via the sphingomyelin/ceramide pathway in various brain cells, including human and rat primary neurons (Jana and Pahan, 2004;Ju et al, 2005;Malaplate-Armand et al, 2006), rat oligodendrocytes (Cheng et al, 2003;Lee et al, 2004;Malaplate-Armand et al, 2006;Zeng et al, 2005), rat astrocytes and glial cells (Ayasolla et al, 2004), and murine neuroblastoma cells (Satoi et al, 2005). Calcium-dependent phospholipase A (cPLA) (Malaplate-Armand et al, 2006), inducible nitric oxide synthase (iNOS) (Ayasolla et al, 2004;Zeng et al, 2005), the p75 neurotrophin receptor (p75NTR) (Costantini et al, 2005), and NADPH oxidase (Jana and Pahan, 2004) have each been shown to be involved in the Aβ-related activation of the sphingomyelin/ceramide pathway. Tumor necrosis factor-alpha (TNF-α) (Ayasolla et al, 2004;Zeng et al, 2005) and interleukin-6 (Fiebich et al, 1995) also are involved in Aβ-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo, where contributing factors relating to microglia-derived reactive oxygen species and cytokines, such as tumor necrosis factor-␣ (TNF-␣) are present, the selective impact on mature myelinating oligodendrocytes could be greater. In fact, Zeng and colleagues have shown that A␤ enhances TNF-␣-mediated oligodendrocyte demise through a sphingomyelinase/ceramide pathway, 43 while our laboratory has previously reported enhanced levels of TNF-␣ within the brains of 3ϫTg-AD mice at ages identical to when oligodendrocyte/myelin deficits become evident.…”
Section: Discussionmentioning
confidence: 99%
“…120 Ab also indirectly contributes to oxidative stress by upregulating inducible nitric oxide synthase (iNOS) in mature OLs through a TNF-a-mediated ceramide pathway. 121 Finally, injection of Ab into the corpus callosum of rats induced myelin damage and OL apoptosis. In this experiment, activated microglia were also seen, 122 further implicating pro-inflammatory molecules such as TNF-a.…”
Section: Ols and Diseasementioning
confidence: 99%